Maternal employment and exclusive breastfeeding in Indonesia: data analysis of IFLS 4 and 5 - Rini, Ika Sulistya; Hasanbasri, Mubasysyir; Hakimi, Mohammad (BKM Public Health and Community Medicine, 2021)
Purpose: One of the key barriers to exclusive breastfeeding is the increasing number of mothers who work outside the home. This study aimed to analyze the relationship between maternal employment and exclusive breastfeeding in Indonesia using data from the Indonesian Family Life Survey (IFLS) 4 and 5. Methods: This study employed an analytic observational design with a cross-sectional approach. The sample consisted of women aged 15–49 years who were never married and currently breastfeeding. Data from IFLS 4 and 5 were analyzed using Chi-square tests and logistic regression to examine the relationship between maternal employment status and exclusive breastfeeding. Results: The percentage of exclusive breastfeeding increased by approximately 10% between 2007 and 2014 (from 10.4% to 22%). During the same period, the percentage of working mothers also increased by about 20% (from 70.3% to 95.2%). In 2007, the highest proportion of breastfeeding working mothers was among private employees (13.5%), while in 2014, it was among those working in informal agricultural jobs (39.3%). There was no statistically significant relationship between maternal employment status in general and exclusive breastfeeding (p>0.05). However, there was a significant association between knowledge of exclusive breastfeeding and exclusive breastfeeding practices (p<0.05). Conclusion: Exclusive breastfeeding rates in Indonesia are affected by maternal knowledge about exclusive breastfeeding.